Vocational Bias and Gender: Evaluations of High School Counsellors by Canadian University Undergraduates - Tomini, Brenda A. (Canadian Journal of Counselling and Psychotherapy, 1992)
Two hundred first-year university undergraduates, 136 females and 64 males, responded to a questionnaire assessing evaluations of career counselling experiences during their previous (high school) year. Responses assessed subjects' career aspirations, career confidence, assessment of persons most important to career choice, and other experiences with high school counsellors. Females generally reported experiences as more favourable than those of males, although females showed lower levels of confidence regarding chosen careers. Student responses did not appear to reflect major problems in terms of gender bias among counsellors, yet the overall evaluations of counselling were largely negative. Comments are offered in light of recent research on gender and related variables in the counselling of young persons.